Developing intentionality and researching multilingually: An ecological and methodological perspective. (November 2013) - Stelma, Juup; Fay, Richard; Zhou, Xiaowei
Abstract : This paper uses an ecological perspective to understand a researcher's developing intentionality vis‐à‐vis her multilingual engagement with research processes, namely, 'researching multilingually'. The paper discusses ecological thinking in Applied Linguistics, ecological themes present in the literature addressing aspects of researching multilingually, and the particular understanding of intentionality we have employed. The potential of intentionality as an heuristic for understanding researching multilingually is explored with reference to a recent research experience of one of the authors – Xiaowei Zhou. This includes analyses of Xiaowei's developing awareness of linguistic possibilities, associated research‐relevant affordances, and her articulation of the intentionality of researching multilingually. We suggest that the combination of an ecological perspective and a focus on intentionality provides a unique methodological understanding of researching multilingually.